Managing paradoxical tensions in the development of a telemedicine system. Issue 1 (March 2022) - Agarwal, Neha; Soh, Christina; Yeow, Adrian
Abstract: The global pandemic has escalated the demand for telemedicine systems across the world, particularly for vulnerable populations such as the elderly in nursing homes. However, challenges in implementation and high failure rates continue to affect the sustainability and capability of telemedicine systems. This study therefore addresses the question of how to sustain and develop telemedicine systems, and offers a conceptual model developed from longitudinal study data and paradox theory. We found that in the inter-organizational context of telemedicine systems, paradoxical tensions arise from conflict between demands and interests of the telemedicine system versus those of its members. We also identified when the specific tensions of belonging, learning, organizing, and performing are likely to occur. These tensions are addressed through responses, initiated by the hub, that address both system and member level demands and interests through creating collaborative governance, uplifting member capabilities, and targeted resourcing. We further demonstrate the temporal dynamics of how the hub's responses create inter-organizational norms and structures that in turn influence responses to tensions in subsequent phases. We examined variations in members' reactions to the responses, and found that they were influenced by member-specific resource factors, suggesting that while the hub does sustain the development of the telemedicine system through addressing common member demands, there are limits with regard to aspects that are more member-specific. Finally, we show how technology can be both enabler-trigger and enabler-response due to its inherent attributes of malleability and reconfigurability. Highlights: Our study offers a conceptual model grounded on paradox theory to deal with the problem of sustaining telemedicine systems. Hub needs to enact both-and responses to manage paradoxical tensions in different phases to sustain the telemedicine system. Hub's responses create inter-organizational norms and structures that influence responses to tensions in subsequent phases. Members' reactions to hub's responses are influenced by their specific resource factors. Technology can be an enabler-trigger and enabler-response due to its attributes of malleability and reconfigurability.